Patterning artificial lipid bilayer on nanostructured surfaces - Ghosh Moulick R (Dove Medical Press, 2018)
Ranjita Ghosh Moulick,1 Gregor Panaitov,2 Sung-Eun Choi,2 Dirk Mayer,2 Andreas Offenhäusser2 1School of Physical Science, Jawaharlal Nehru University, New Delhi, India; 2Bioelectronics, ICS8/PGI8, Forschungszentrum Juelich, Juelich, Germany Abstract: Artificial lipid bilayer on solid substrate plays an important role as an interface between nanotechnology and biology. In this study, grid structures were patterned on Au-Nb-glass substrate and artificial bilayer was prepared on these structures. The fluidity was checked using fluorescence recovery after photobleaching (FRAP), and neuronal adhesion was monitored on such structure using EphrinA5-tethered lipid bilayer. EphrinA5 is a ligand that binds to the Eph receptors of rat cortical neurons and influences cellular adhesion. Our result elucidated that influence of these nanopatterned protein-tethered lipid bilayer on cellular guidance and signaling can address many underlying mechanisms of cellular functioning and help us to understand and differentiate the signaling procedure in cancer and neurodegenerative diseases. Keywords: Au-Nb, FRAP, EphrinA5, lipid bilayer, neurodegenerative diseases